Kompország városai. (Történeti régiók és városok) - Beluszky, Pál (Tér és Társadalom, 1996)
The author aims at evaluating the changing position of Hungary in the historical regions and the impact of this situation on urban development. The starting point of the author is generally accepted notion, that two basic types of (societal) development appeared in Europe, a Western and an Eastern Eupopean one. The former was based on a mixture of the antique (Roman) and Germanic heritage, its economic basis was the indisputable private ownership of land with the various classes of the divided feudal society held together by a clear system of rights and obligations. In Eastern Europe the working layers had hardly any right to the land that they tilled, the feudal system only appeared in part. It was not only the serves, but also the noblemen who were dependents of the state power (the ruler) without any legal regulation. The territory of two types of development changed during the course of history and a border zone formed between the "core regions" of these types. Hungary was mainly situated in this border zone.